2020
DOI: 10.1111/jfpp.15024
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive peptides with multiple activities extracted from Barley (Hordeum vulgareL.) grain protein hydrolysates: Biochemical analysis and computational identification

Abstract: Plant‐derived bioactive peptides demonstrate great potential given their availability and cost‐effectiveness. In this study, barley (Hordeum vulgare L.) grain proteins were explored for bioactive peptides with potential health applications. Gross grain proteins were obtained through aqueous extraction, after which, trypsin hydrolysis was performed. The hydrolysis process provided high peptide yields reaching 11%. The peptide hydrolysates were evaluated for their antioxidant and metal chelating activities, DPP4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Hence, studies have focused on discovering and utilising antioxidant peptides from natural sources such as plants, seeds, meat, fish, etc ., as an alternative to synthetic molecules. Some studies demonstrated the potential of whole barley consumption or proteins and bioactive peptides extracts as potential T2D treatments in vitro and in vivo (Tok et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, studies have focused on discovering and utilising antioxidant peptides from natural sources such as plants, seeds, meat, fish, etc ., as an alternative to synthetic molecules. Some studies demonstrated the potential of whole barley consumption or proteins and bioactive peptides extracts as potential T2D treatments in vitro and in vivo (Tok et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Bioinformatics has become a significant component in bioactive peptide studies. They are used to predict the potential presence of bioactive peptides inside a specific protein sequence and knowledge about targets and enzymes (Tok et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the beverage industry, where indignant alcohol consumption has been positively correlated to induce excessive production of ROS, resulting in liver damage, fermented barley is a healthier choice. Fermented barley extracts are linked to improving antioxidant activities by assuaging alanine aminotransferase and aspartate aminotransferase levels [ 56 , 91 , 92 ]. Additionally, fermented barley extracts were shown to suppress IL-1, IL-6, and tumor necrosis factors in lipopolysaccharide (LPS)-induced inflammation in rats, thus reiterating the anti-inflammatory activities of barley extracts [ 91 ].…”
Section: Cereals Historical Significance and Assortmentsmentioning
confidence: 99%
“…The fundamental principle of the anti-inflammatory effects of fermented barley extracts was related to the upregulation of antioxidant enzyme activities and the downregulation of oxidative stress. From the aforementioned, it is evident barley has potential benefits in fighting inflammation-related diseases [ 56 , 92 ].…”
Section: Cereals Historical Significance and Assortmentsmentioning
confidence: 99%